2003
DOI: 10.1073/pnas.0237108100
|View full text |Cite
|
Sign up to set email alerts
|

Expression and assembly of a fully active antibody in algae

Abstract: Although combinatorial antibody libraries have solved the problem of access to large immunological repertoires, efficient production of these complex molecules remains a problem. Here we demonstrate the efficient expression of a unique large single-chain (lsc) antibody in the chloroplast of the unicellular, green alga, Chlamydomonas reinhardtii. We achieved high levels of protein accumulation by synthesizing the lsc gene in chloroplast codon bias and by driving expression of the chimeric gene using either of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
165
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(173 citation statements)
references
References 20 publications
3
165
0
5
Order By: Relevance
“…Several studies have already demonstrated that the green alga C. reinhardtii is a convenient platform for producing recombinant proteins, including those of human origin (23). For example, a large single-chain antibody directed against glycoprotein D of the herpes simplex virus (24) and full-length IgG1 monoclonal antibodies directed against anthrax protective antigen 83 (25) have been successfully expressed in the chloroplast of transgenic C. reinhardtii cells. The production of secreted therapeutic proteins such as erythropoietin has also been evaluated (26).…”
mentioning
confidence: 99%
“…Several studies have already demonstrated that the green alga C. reinhardtii is a convenient platform for producing recombinant proteins, including those of human origin (23). For example, a large single-chain antibody directed against glycoprotein D of the herpes simplex virus (24) and full-length IgG1 monoclonal antibodies directed against anthrax protective antigen 83 (25) have been successfully expressed in the chloroplast of transgenic C. reinhardtii cells. The production of secreted therapeutic proteins such as erythropoietin has also been evaluated (26).…”
mentioning
confidence: 99%
“…We showed that a gD-Dendra2 fusion protein localized primarily to the cell surface in the presence or absence of an anti-gD antibody under non-ABB conditions (8); thus, we could use this protein to investigate the fate of a cell surface antigen under ABB conditions. We used an anti-gD IgG antibody (20) with a human Fc (anti-gD hFc ) that can bind to gE-gI and to gD to create ABB complexes and two types of control IgGs to create non-ABB complexes: the anti-gD antibody fused with a mouse Fc (antigD mFc ), which binds gD, but not gE-gI; and a human IgG against an unrelated antigen (IgG hFc ), which binds gE-gI, but not gD (Fig. 1).…”
mentioning
confidence: 99%
“…Successful expression and assembly of a recombinant human monoclonal IgA antibody has already been demonstrated for Chlamydomonas reinhardtii [6], while stable expression of the hepatitis B surface antigen gene has been shown in Dunaliella salina [7]. Since Dunaliella is otherwise used for nutrition, there is no need for purification of the antigen, so the intact algae could be used to deliver a vaccine.…”
Section: Antibody and Vaccine Productionmentioning
confidence: 99%